Orgafig® daily intake minimizes oxidative stress and tissue damage in the liver in the face of challenges with aflatoxin in the diet and consecutive doses of acetaminophen - Marchiori M.S.* (2022)
© 2022, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.This study aims to evaluate whether the consumption of homeopathic products (Orgafig®) in Wistar rats (Rattus norvegicus) can protect the liver against two challenges (a) antipyretic/analgesic (acetaminophen), and (b) feed contaminated with aflatoxin B1. We used 60 animals divided into six groups of ten animals each (a) negative control (NC) that did not receive the drugs and was not challenged with aflatoxin B1; (b) negative control + Orgafig® (NC -H) receiving only homeopathy; (c) positive control for aflatoxin B1 (CP-A) receiving a mycotoxin-contaminated diet; (d) positive control for acetaminophen (CP-P) receiving daily doses of the drug orally; (e) Orgafig® + aflatoxin (HA) receiving homeopathic and challenged with diet contaminated with aflatoxin B1; and (f) Orgafig® + acetaminophen (HP) receiving homeopathic and were challenged with doses of acetaminophen. The Orgafig® was added to the diet for 32 days before the challenge with preventive intent. Then, a challenge was conducted over 10 days using aflatoxin B1 via diet and oral acetaminophen doses. Rats that consumed aflatoxin grew more slowly than the other groups. There were increases in serum activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (AP), indicating liver damage in animals from the positive control groups (CP-A and CP-P); this did not occur in animals with preventive use of Orgafig® (HA and HP). Likewise, in the liver, there was an increase in cell injury and oxidative stress biomarkers (reactive oxygen species, thiobarbituric acid reactive substances, and glutathione S-transferase) that also signal liver damage in the positive control rats (CP-A and CP-P); this did not occur in animals with preventive or Orgafig® use (HA and HP). These results suggest that the prophylactic use of the Orgafig® minimizes the adverse effects caused by the daily consumption of aflatoxin B1 and acetaminophen, which are known for hepatotoxic action when used in high doses or for prolonged periods.